Analisis Daya Saing Ekspor Komoditas Mangga Terhadap Pertumbuhan Ekonomi Indonesia - Tambunan, Greyuni Grace; Dahri Tanjung; Nurlela (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Indonesia as a mango producer is exported to various countries around the world. The main destination countries for mango exports from Indonesia are Singapore and Malaysia. This research data was analyzed using the Revealed Comparative Advantage (RCA), Export Product Dynamic (EPD), and Export Competitiveness Index (ECI) methods using data for the 2017-2022 period. The RCA results show an increase in mango competitiveness to Singapore in 2019 and a decrease due to the COVID-19 pandemic. EPD indicates the position of Indonesian mangoes as a